Left-Sided Diverticulosis is a Risk Factor for Distal Colon Polyps - Shashank Sarvepalli (Shiraz University of Medical Sciences, 2020)
BACKGROUND AND AIMS Previous small to mid-sized studies have found an inconsistent relationship between diverticulosis and colon polyps. We assessed the odds of polyps in patients with left-sided diverticulosis (LDV) compared to patients without LDV, and if a predilection for polyps in the distal colon (DC) versus the proximal colon (PC) existed. METHODS In this case-control, retrospective study records of all patients in the Cleveland Clinic undergoing average-risk, screening colonoscopy between January 2011-August 2017 were identified. Baseline characteristics were described. Multivariate logistic regression analysis was performed to identify odds of polyps in PC and DC after adjusting for clinical and colonoscopic factors. RESULTS 50,703 patients (mean age=60 years; 48% male) were included; 38.9% of patients had LDV. Compared to patients without LDV, those with LDV more often had adenomas (33.2% vs 27.8%; p <0.001), hyperplastic polyps (HPs) (18.3% vs 16.2%; p <0.001), and sessile serrated polyps (SSPs) (4.8% vs 4.3%; P=0.011). LDV was associated with adenomas in the DC (OR, 1.59; 95%CI, 1.52, 1.67) more than the PC (OR, 1.15; 95%CI, 1.10, 1.21), with HPs equally in the PC (OR, 1.27; 95%CI, 1.20, 1.34) and DC (OR, 1.28; 95%CI, 1.19, 1.38), and with SSPs in the DC only (OR, 1.50; 95%CI, 1.34, 1.67). CONCLUSIONS LDV is associated with a significantly increased risk of adenomas, HPs, and SSPs, but the association was stronger for adenomas in the DC. Careful inspection of the DC should be encouraged in patients with LDV. More research is needed to understand this phenomenon.